Quasi-static Multilayer Electrical Modeling of Human Limb for IBC - S. H. Pun (Journal of Systemics, Cybernetics and Informatics, 2011)

(untitled)
Home health care system and long term physiologic parameters monitoring system are important for elevating the living quality of chronic disease patients and elderly. Elaborating towards a sophisticated and comprehensive home health care system, Intra-Body Communication (IBC) is believed to have advantages in power consumption, electromagnetic radiation, interference from external electromagnetic noise, security, and restriction in spectrum resource. In this article, we start from quasi-static Maxwell